Molecular identification and genetic studies in Peruvian Phragmipediums - Rolando, Isaias (2015)
Peru has inherited one of the greatest biodiversities of the planet. The orchid genus Phragmipedium has several representatives in the country. They are listed in Appendix 1 of CITES, restricted from international trade.